Correction: Machine learning-based e-commerce platform repurchase customer prediction model. - Cheng-Ju Liu; Tien-Shou Huang; Ping-Tsan Ho; Jui-Chan Huang; Ching-Tang Hsieh (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0243105.].